The effect of forest establishment on biodiversity and ecosystem function - Warner, E (2021)
Forest expansion is increasingly proposed as a mechanism to tackle the biodiversity and climate crises. It is therefore crucial we understand the impacts of forest establishment on biodiversity and ecosystem functions, so that we can optimise future forest creation.